2017
DOI: 10.1016/j.epsl.2017.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Production of nanoparticles during experimental deformation of smectite and implications for seismic slip

Abstract: Nanoparticles and amorphous materials are common constituents of the shallow sections of active faults. Understanding the conditions at which nanoparticles are produced and their effects on friction can further improve our understanding of fault mechanics and earthquake energy budgets. Here we present the results of 59 rotary shear experiments conducted at room humidity conditions on gouge consisting of mixtures of smectite (Ca-montmorillonite) and quartz. Experiments with 60, 50, 25, 0 wt.% Ca-montmorillonite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 44 publications
7
47
1
Order By: Relevance
“…1a), quartz peaks appear in the Raman transect in the center ∼50% of the diameter, and in the outer rim of wear material, the powder is more evenly distributed. This observation of increased wear and amorphization at higher slip speeds is similar to previous experiments on clay-quartz mixtures 19 .…”
Section: Resultssupporting
confidence: 91%
“…1a), quartz peaks appear in the Raman transect in the center ∼50% of the diameter, and in the outer rim of wear material, the powder is more evenly distributed. This observation of increased wear and amorphization at higher slip speeds is similar to previous experiments on clay-quartz mixtures 19 .…”
Section: Resultssupporting
confidence: 91%
“…an aseismic regime) at slow slip-rates to velocity weakening (i.e. seismic) at high slip-rate (Faulkner et al, 2011;Aretusini et al, 2017). (Faulkner et al, 2011) have postulated that this switch is due to thermal pressurization of pore fluid in the clay.…”
Section: Implication In Terms Of Triggered "Ultra-shallow" (< 2 Km) Smentioning
confidence: 99%
“…However, recent results from laboratory experiments on clays at high slip-rates (i.e. >2 m/s) 50,51 have shown that clays can react seismically to rupture that propagates into it, one such example being the 2011 Tohoku earthquake where 30 m of slip is estimated to have occurred in clay like material 52 . A similar scenario could apply to explain the ultra-shallow events that occurred at depths of less than a few hundred meters.…”
Section: Introductionmentioning
confidence: 99%